Buhay mascot mga babae ng Santiago - Aguilar, Mila; Lee, Ricardo (Pinoy Tok, 1989)
The first episode is a 15 minutes show of commercial mascots, their use and manufacture and the people who operate them. The second episode is a 15 minutes portrait of 1992 presidential candidate Senator Joseph Estrada, including his presidential plans. The last is a 20 minutes show of the women of Santiago, Isabela who have married Japanese farmers for a fee.